RANCANG BANGUN SOUNDINGMETER FUEL OIL KAPAL PENANGKAP IKAN BERBASIS MIKROCONTROLLER ATMEGA328 - Sobri; Basino; Pungkas Prayitno; Ade Hermawan; Afifudin (Bajang Institute, 2022)
This study discusses the design of a sounding system that measures the liquid contents in a vessel tank. The fuel tank sounding system on the ship still uses manuals. In this case it can be a problem that is often faced because it has not used an automated system. Monitoring the measurement of the level of fuel in the tank using a measuring line. In this Final Project a fuel tank monitoring model has been designed on the ship using the application of ultrasonic waves by reflecting sound waves. This monitoring model is to make a system know if the fuel in the tank on the ship has started to run out. The device system consists of a transmitter, an ultrasonic receiver based on the ATMega326 microcontroller. Transmitter and receiver are directed to the tank. Where the distance is directly proportional to the transmitter's transmitting time until it is received back by the receiver, then processed using the ATMega326 microcontroller as the main controller, and the LCD as a display of the state of the fuel that is in the tank of the ship.